Successful pregnancy in a South African patient with end-stage renal disease with the use of thrice-weekly nocturnal haemodialysis - Stead, Piers A; Bapoo, Nabeel A; Grobbelaar, Ronell; Miller, Derek; Dumbril, Douglas (African Journal of Nephrology, 2017)
Pregnancy outcomes in patients on chronic dialysis have improved as a result of the intensification of dialysis and improved perinatal care. We report the successful outcome of a pregnancy in a patient on chronic haemodialysis in Cape Town, South Africa. With intensification of her therapy using thrice-weekly, nocturnal haemodialysis the pregnancy was maintained until 34 weeks at which time a 1.86 kg baby boy was delivered by elective caesarean section. One year later the patient was doing well on maintenance haemodialysis and the baby was achieving his developmental milestones. This report highlights our ability to employ a multi-disciplinary approach and prolonged, nocturnal haemodialysis to support pregnant dialysis patients in the South African setting and achieve good outcomes for both mother and baby.